2009
DOI: 10.17796/jcpd.34.2.96656211337v7517
|View full text |Cite
|
Sign up to set email alerts
|

Pulp Polyp Associated with a Natal Tooth: Case Report

Abstract: Natal teeth are an infrequent occurrence at birth. Often these teeth are extracted because they are very mobile and pose a risk of aspiration. This is a rare case in which a natal tooth was extracted by the pediatrician with his fingers. A root fragment remained and out of this developed a large pulp polyp. This relationship has not been previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…They termed this structure a residual natal tooth. It was also reported that a natal tooth was extracted by the paediatrician with his fingers and a root fragment remained from which developed a large pulp polyp 34 . Agostini et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They termed this structure a residual natal tooth. It was also reported that a natal tooth was extracted by the paediatrician with his fingers and a root fragment remained from which developed a large pulp polyp 34 . Agostini et al.…”
Section: Discussionmentioning
confidence: 99%
“…They termed this structure a residual natal tooth. It was also reported that a natal tooth was extracted by the paediatrician with his fingers and a root fragment remained from which developed a large pulp polyp 34 . Agostini et al 24 reported a case of an uncommon hamartoma affecting a 4-month-old Caucasian male patient, who previously displayed two natal teeth at the same location.…”
Section: Natal Teethmentioning
confidence: 99%
“…Natal tooth associated with benign reactive lesion has been described in the literature by Muench et al [3] and Agarwal et al [4] reported a case of pyogenic granuloma. Singh et al [2] reported a case of reactive fibrous hyperplasia, pulp polyp by Vergotine [5] and POF by Kohli [6] and Ravindranath. [7] Ossifying fibroid epulis, peripheral fibroma with calcification, peripheral cemento-ossifying fibroma, calcifying fibroma, peripheral cementifying fibroma, ossifying fibro-epithelial polyp, peripheral fibroma with osteogenesis, peripheral fibroma with cementogenesis, peripheral fibroma with calcification, calcifying or OFE, and calcifying fibroblastic granuloma are all terms that have been used to refer to POF.…”
Section: Discussionmentioning
confidence: 99%
“…1,11,48 Eğer küretaj uygulanacaksa yeterli anestezi sağlanması adına lokal anestezi yapılması gerekmektedir. 46 Yetersiz küretaj nedeniyle % 9.1 rezidüel neonatal diş gelişimi, 46,49 mikst kalsifiye hamartoma, 50 sürmüş kalıntılar olarak pulpa polipi, 51 çekim esnasında travmaya bağlı olarak piyojenik granüloma ve periferik ossifying fibroma 52 rapor edilmiştir.…”
Section: Prevalansunclassified